The role of biopores with organic materials in improving soil properties and tea productivity in degraded land - Febryani, Mita Amelia; Wulansari, Restu; Muliani, Yenny (Journal of Degraded and Mining Lands Management, 2026)
Tea plants (Camellia sinensis (L.) O. Kuntze) are highly influenced by environmental conditions, particularly water availability and soil quality. Climate change and intensive cultivation practices have accelerated the degradation of tea plantation soils, characterized by high soil compaction, low porosity, acidic pH, and a decline in organic matter and nutrient content. These conditions result in reduced soil water infiltration, stunted growth, and lower-quality tea shoots. Previous studies have primarily focused on hydrological aspects, particularly infiltration, without linking improvements in soil properties to plant productivity. This study aimed to examine the role of biopore infiltration holes (BIPs) made with various organic materials on infiltration rates, soil moisture content, and tea shoot production and quality in degraded land. The study employed a randomized block design with 10 treatments and three replications. The results indicate that the application of biopores significantly increased soil infiltration rates to moderate to very fast levels and improved soil physical and chemical properties by enhancing porosity, aggregate stability, and organic carbon and total nitrogen content. However, the application of biopores did not significantly affect tea shoot production in the short term, as the decomposition of organic matter and microbial activity require time before nutrients become available to the plants.